A grim reaper's guide to cheating death - Dara, Maxie (A S.C.Y.T.H.E. Mystery, 2025)
"When a determined killer targets her brother, a grim reaper risks everything to save him in this delightful cozy mystery. Nora Bird works for S.C.Y.T.H.E., which might seem odd for someone as terrified of death as she is. But ever since her parents died in an accident when she was six, she's been obsessed with avoiding risk, and what better place to learn how to cheat death than the company that employs the nation's grim reapers? The work enables Nora to learn all about the myriad ways you can kick the bucket, which is comforting...until one day, a file crosses her desk with a name she recognizes. Her twin brother's. The twins haven't spoken in six months, but Charlie is all Nora has left. Completely against her cautious nature, Nora steals the file and flees, racing to her brother's house. She begs him to trust her that his death is imminent, and they hit the road (with his parrot, Jessica, who has plenty to say) in an attempt to evade both death and S.C.Y.T.H.E., whose sole mission of collecting souls has been disrupted by Charlie's continued existence. Alas, every time Nora saves him, a new cause of death appears in his file. Someone is determined to take Charlie out, and Nora will have to use everything she's ever learned about death to discover the culprit"--